Determination Of Development Inequality Between Regions On The Island Of Sumatra - M. Khaikal Andeski; Zulgani Zulgani; Putri Intan Suri (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to analyze the condition and influence of urban hierarchy, road density, and the Human Development Index (HDI) on economic development inequality among regions in Sumatra Island during the period 2019–2024. Development inequality in Sumatra remains considerably high, as reflected by the significant disparities in economic growth rates, infrastructure quality, and human resource quality across provinces. This study employs secondary panel data from ten provinces in Sumatra, analyzed using panel data regression. Based on the Chow Test and Hausman Test, the Fixed Effect Model (FEM) was selected as the most appropriate model. The results indicate that partially, only the urban hierarchy variable has a positive and significant effect on economic development inequality, suggesting that the better and more structured the urban hierarchy of a province, the more evenly distributed its economic activities tend to be across regions. Meanwhile, road density and HDI do not show significant partial effects. Simultaneously, all independent variables together have a significant effect on economic development inequality, with the model demonstrating a very high ability to explain the variation in inequality across provinces. This study recommends the development of new growth centers beyond major cities, more equitable road infrastructure development toward remote areas, and the acceleration of human resource quality improvement in provinces with low HDI.